(untitled) (Bangladesh Journal of Radiology and Imaging, 2026)
Background: Chronic venous disease (CVD) is a progressive disorder characterized by venous reflux, valvular incompetence, and venous hypertension. The CEAP (Clinical–Etiological–Anatomical–Pathophysiological) classification system, updated by the Society for Vascular Surgery and American Venous Forum, provides standardized staging. Duplex ultrasound remains the gold standard for hemodynamic assessment. Objective: To evaluate venous reflux patterns using duplex Doppler ultrasound and correlate imaging findings with CEAP clinical classification. Methods: This prospective observational study included 86 patients with clinically suspected CVD. Patients were categorized according to CEAP clinical class (C2–C6). B-mode, color, and spectral Doppler ultrasound were performed to assess reflux duration, reflux velocity, venous diameter, valvular competence, and presence of deep vein thrombosis (DVT). Statistical analysis included Chi-square test, ANOVA, and Pearson correlation. Results: Great saphenous vein (GSV) reflux was detected in 72.1% of patients. Prolonged reflux (>0.5 sec) was significantly associated with higher CEAP classes (C4–C6) (p < 0.05). Mean reflux duration increased progressively with disease severity. Venous diameter positively correlated with CEAP class (r = 0.62). DVT was identified in 18.6%, predominantly in advanced CEAP stages. Conclusion: Integration of duplex ultrasound findings with CEAP classification enhances disease stratification and prognostic evaluation in CVD. Reflux duration and venous diameter may serve as imaging biomarkers of advanced venous disease.